2017
DOI: 10.3389/fmicb.2017.02016
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Widespread Associations between Neotropical Hymenopteran Insects and Actinobacteria

Abstract: The evolutionary success of hymenopteran insects has been associated with complex physiological and behavioral defense mechanisms against pathogens and parasites. Among these strategies are symbiotic associations between Hymenoptera and antibiotic-producing Actinobacteria, which provide protection to insect hosts. Herein, we examine associations between culturable Actinobacteria and 29 species of tropical hymenopteran insects that span five families, including Apidae (bees), Vespidae (wasps), and Formicidae (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 73 publications
(90 reference statements)
4
50
0
2
Order By: Relevance
“…In this study, the diversity of culturable ant-associated actinobacteria obtained from three ant species is investigated. Our results have shown that the actinobacterial community is diverse and that the most abundant genus recovered is Streptomyces, which is consistent with previous reports (Matarrita-Carranza et al, 2017). It is worth noting that such large amounts of rare actinobacterial genera and novel taxa isolated from ant samples have not been previously reported.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In this study, the diversity of culturable ant-associated actinobacteria obtained from three ant species is investigated. Our results have shown that the actinobacterial community is diverse and that the most abundant genus recovered is Streptomyces, which is consistent with previous reports (Matarrita-Carranza et al, 2017). It is worth noting that such large amounts of rare actinobacterial genera and novel taxa isolated from ant samples have not been previously reported.…”
Section: Discussionsupporting
confidence: 93%
“…It might be because the isolation media used in this study presents a bias that favored the growth of Streptomyces strains. Other studies also demonstrated that Streptomyces was the most commonly isolated genus from soil, plant and insect environments using these media, although many rare actinobacteria genera were also recovered (Matsukawa et al, 2007;Qin et al, 2012;Kaewkla and Franco, 2013;Matarrita-Carranza et al, 2017). The interaction between members of the genus Pseudonocardia in the family Pseudonocardiaceae and fungus-growing ants has been extensively reported (Currie et al, 1999;Andersen et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations